Clinical Characteristics and Outcome of Pediatric Cases Managed During the First Wave of the Covid-19 Pandemic at Ahmadu Bello University Teaching Hospital, Zaria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Over 161 million cases of COVID-19 have so far been confirmed globally with over 3.3 million deaths. An understanding of the local epidemiological characteristics in the pediatric population is necessary to enable proper planning of mitigation strategies.Aim:To describe the clinical characteristics and outcomes of pediatric patients with COVID-19.Setting and Design:We conducted a retrospective study on cases of COVID-19 diagnosed by the real-time polymerase chain reaction of nasopharyngeal samples and oropharyngeal swabs managed during the first wave of the pandemic at the Ahmadu Bello University Teaching Hospital. The severity of illness was graded based on clinical features as classified by the World Health Organization. Statistical Analysis was carried out using IBM SPSS Version 23 (California, USA).Results:Forty-six children met the above criteria. The median age was 7 yrs (IQR = 3.75-12). There were more females than males with Covid-19 infection (M:F = 1:1.55). A third (32.6%) of children were asymptomatic while half (50%) had only mild symptoms. Although school-aged children aged 6-11 years were the most infected (30.4%), more severe disease was seen in infants (25%) and those with co-morbidities. Nasal discharge, cough, and fever were the most common presentation occurring in 34.8%, 32.6%, and 26.1%, respectively. The case fatality rate was 6.5%, all occurring amongst those with comorbidities.Conclusion:COVID-19 infection in children is largely mild or asymptomatic. Symptoms when present are indistinguishable from symptoms of other common viruses causing upper respiratory tract infections. Severe disease and mortality were observed among infants and children with co-morbidities.